High-performance flexible thermoelectric generator with hydrogel-copper foam cooling for self-powered wearable electronics - Hejia Wang; Wei Wang; Gang Li; Dessalegn Abera Waktole; Zhengxing Zuo; Boru Jia; Huihua Feng; Mengyu Wang; Shuaiyue shao (Case Studies in Thermal Engineering)
Flexible thermoelectric generators (FTEGs) harvesting body heat offer a sustainable energy solution for wearables but traditional FTEGs suffer from insufficient power density under natural convection. This study introduces an innovative FTEG with hydrogel-copper foam composite sinks to boost heat dissipation and power output. The hydrogel, embedded in copper foam, leverages the foam's high thermal conductivity and the hydrogel's three-dimensional porous structure to enhance evaporative cooling, while the addition of LiCl enables a long-lasting evaporation–hygroscopic cycle. The FTEG achieves a power density of 167.7 μW/cm2 (2.5 m/s wind speed, ΔT = 20 °C) and 95.4 μW/cm2 under natural convection, 29 × higher than previous results using traditional cooling sinks. The FTEG maintains excellent flexibility, with less than 1 % internal resistance changes after 1000 bending cycles. It successfully powers an electrocardiogram (ECG) sensing system in real-time, generating 83 mV and 840 μW under natural convection using an LTC3108 chip and AD8233 sensor, with 27.98 % power conversion efficiency. The system operates solely on body heat, eliminating the need for batteries or supercapacitors. These results highlight the FTEG's potential for sustainable, efficient wearable electronics.